Multi-touch exploration of CT medical data with an iPad - Lim, Kah Heng. (2013)
Medical Computed Tomography (CT) scan has been widely used to give physicians a better picture of the patients’ medical condition. This technology made many preventive treatments possible. However, the scan data is a compilation of 2-Dimensional (2D) slices taken in rapid succession to form a detailed 3- Dimensional (3D) representation of the body.